(untitled) (Journal on studies and research of academic knowledge, 2013)
The situation of older people in Paraguay is a concern result of cumulative annual population growth of 3.2%, increased life expectancy and sustained decrease in birth rates and mortality. The first public actions in this area date from 1915 with the founding of Almshouse enabled the majority from 1950 to 1970. The Almshouse "Santa Maria of Encarnación City performs its functions since 1961, under the supervision of the Salesian Sisters of the Sacred Heart of Jesus. The present work, prospective cross, sought to know the self-sufficiency in basic activities of daily living. fall risk assessment laboratory profile of the elderly, meeting, which is a heterogeneous group in age balanced in terms of gender. Dependent in at least 4 of the 6 activities of daily living according Barthel scale in 27%. The extrinsic risk of falls, is almost zero by building characteristics and athough we found anemia in 43% of the elderly, and elevated LDL cholesterol levels by 46%, blood pressure and creatinine are normal in 100% of them.